Characteristics of highest quality zaytun oil and its benefits : an analysis of Quranic exegesis and scientific findings - Nur Syamila Romli (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
Zaytun oil has long been considered one of history's most beneficial food products. Unfortunately, it is also one of the most adulterated food products in the world due to its relatively low cost of production vis-a-vis higher selling prices as compared to other vegetable and seed oils. The manufacturing and sale of counterfeit zaytun oil have been going on for thousands of years. In addition to the lack of health advantages, counterfeit, and low quality of zaytun oil is also capable of causing damage to consumers; and as for the real extra virgin zaytun oil, various claims have been made asserting that their extra virgin zaytun oil is the best without any concrete substantiation. Therefore, resolving this problem is of vital importance. In light of quranic exegesis and scientific findings, this study has identified a comprehensive analysis of the characteristics of the highest quality zaytun oil by using the library research method. The three key results of this research are: (1) Compulsory specifications and recognition from authorized institutions such as USDA Organic are the best way to select the authentic and genuine zaytun oil; (2) The characteristics of the highest quality extra virgin zaytun oil from the Quranic point of view are revealed from tafsir verses 35 from Surah Al-Nur (24: 35), “Shajaratin Mubarakatin Zaytunatin La Sharqiyyatin Wa La Gharbiyyatin” through the narration of Ibn Abbas, which means: The zaytun tree must be located in the desert or mountain and must not be blocked by the shadow of mountains, other trees, or cave and must be totally exposed to sunlight and heat all day long. Surprisingly, scientific findings indicate that zaytun oil with the greatest hydroxytyrosol (most potent antioxidant) concentration has been discovered from zaytun trees cultivated in Morocco's Atlas Mountains rocky desert areas. Marketed under the brand name Olivie Plus 30x, the oil demonstrates 233 mg/kg hydroxytyrosol, 30 times greater than the standard additional virgin zaytun oil of only 7 mg/kg, the highest rate in the globe, align with the narration of Ibn Abbas since the last thousand years on characteristics of the best quality zaytun oil; (3) Scientific findings on the benefits of zaytun oil on each system on human body prove how amazing the Shajarah Mubarakah could be, a tree enriched with endless benefits gifted from Allah to human being.